Hematite/Polystyrene Raspberry‐Like Microcomposites as Stable Support for Silver Nanoparticle Immobilization. (15th January 2021) - Lupa, Dawid; Oćwieja, Magdalena; Adamczyk, Zbigniew
Abstract: Among the methods utilized for the preparation of raspberry‐like microcomposites, due to its simplicity and universality, the electrostatically‐driven deposition of nanoparticles at the surface of microparticles is especially attractive. This process, leading to the formation of a single nanoparticle monolayer, is widely reported. On the other hand, no data concerning the electrostatically‐driven formation of nanoparticle bilayers at the surface of microparticles are reported. To fill this gap, the detailed investigation of the formation of silver/hematite nanoparticle bilayers at the surface of polystyrene microparticles is reported. First, the hematite/polystyrene raspberry‐like microcomposites are obtained by immobilization of hematite nanoparticles under an electrostatically‐driven process. The stability of hematite/polystyrene microcomposites at elevated temperatures up to 323 K is monitored using microelectrophoresis. No significant changes in the hematite nanoparticle layer coverage are observed after prolonged time of incubation. This proves the irreversible character of nanoparticle immobilization. Next, the hematite/polystyrene microcomposites are utilized as the interfaces for immobilization of negatively charged silver nanoparticles. This process is quantitatively described using electrokinetic measurements. The changes in the hydrodynamic diameter of microcomposites are also determined. Finally, the validity of the electrokinetic model used in this work for predicting the zeta potential of the silver/hematite/polystyrene microcomposites is confirmed. Abstract : Stable raspberry‐like microcomposites obtained in electrostatically‐driven deposition of hematite nanoparticles at polystyrene microparticles are used as support for silver nanoparticle immobilization. This results in the formation of colloidal superstructure‐nanoparticle bilayers at microparticles. Electrokinetic properties of such hybrid particles are determined for different ionic strength and surface coverage values. Experimental results are interpreted in terms of electric double layer interactions.